BnaA.bZIP1 Negatively Regulates a Novel Small Peptide Gene, BnaC.SP6, Involved in Pollen Activity - Wang, Xuanpeng; Li, Xin; Li, Mengmeng; Wen, Jing; Yi, Bin; Shen, Jinxiong; Ma, Chaozhi; Fu, Tingdong; Tu, Jinxing (Frontiers in Plant Science, 2017)
Small peptides secreted to the extracellular matrix control many aspects of the plant’s physiological activities which were identified in Arabidopsis thaliana, called ATSPs. Here, we isolated and characterized the small peptide gene Bna.SP6 from Brassica napus. The BnaC.SP6 promoter was cloned and identified. Promoter deletion analysis suggested that the -447 to -375 and -210 to -135 regions are crucial for the silique septum and pollen expression of BnaC.SP6, respectively. Furthermore, the minimal promoter region of p158 (-210 to -52) was sufficient for driving gene expression specifically in pollen and highly conserved in Brassica species. In addition, BnaA.bZIP1 was predominantly expressed in anthers where BnaC.SP6 was also expressed, and was localized to the nuclei. BnaA.bZIP1 possessed transcriptional activation activity in yeast and protoplast system. It could specifically bind to the C-box in p158 in vitro, and negatively regulate p158 activity in vivo. BnaA.bZIP1 functions as a transcriptional repressor of BnaC.SP6 in pollen activity. These results provide novel insight into the transcriptional regulation of BnaC.SP6 in pollen activity and the pollen/anther-specific promoter regions of BnaC.SP6 may have their potential agricultural application for new male sterility line generation.